2023
DOI: 10.3389/fendo.2023.1161707
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of atosiban for repeated embryo implantation failure: A systematic review and meta-analysis

Abstract: BackgroundRepeated embryo implantation failure (RIF) posed a significant challenge in assisted reproduction. Evidence of its therapeutic effectiveness including atosiban used around embryo transfer to improve pregnancy outcomes in RIF patients undergoing in vitro fertilization-embryo transfer (IVF-ET) remained inconsistent. This study aimed to explore the efficacy of atosiban on pregnancy outcomes of patients with RIF who received IVF-ET. MethodsThe research was designed using the PICOS format. A systematic se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…In 2011, chou et al reported that a lower dosage of atosiban improved pregnancy outcomes of patients with RIF, but the number of recruited patients was small 20 . Another study by Wang et al 33 discovered RIF patients presented with higher clinical pregnancy rates with the administration of atosiban in IVF-ET cycles, without significant changes in ectopic rate, multiple-gestation pregnancy rate, and miscarriage rate. Ng et al 34 found that 800 patients receiving IVF were selected from Guangzhou, Hong Kong, and Ho Chi Minh City and admitted in a multicenter, randomized, and double-blind trial.…”
Section: Discussionmentioning
confidence: 97%
“…In 2011, chou et al reported that a lower dosage of atosiban improved pregnancy outcomes of patients with RIF, but the number of recruited patients was small 20 . Another study by Wang et al 33 discovered RIF patients presented with higher clinical pregnancy rates with the administration of atosiban in IVF-ET cycles, without significant changes in ectopic rate, multiple-gestation pregnancy rate, and miscarriage rate. Ng et al 34 found that 800 patients receiving IVF were selected from Guangzhou, Hong Kong, and Ho Chi Minh City and admitted in a multicenter, randomized, and double-blind trial.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, we used a total dose of 37.5mg atosiban in the study. According to the published data, there have been various types of doses and modes of administration (bolus versus infusion) of atosiban as an adjuvant in ART and they may contribute to the heterogeneity of the studies ( 6 ). Nevertheless, the reviews of previous data ( 6 , 18 ) also suggested that the association between atosiban and ET outcomes is not necessarily linked to the dose of atosiban administration and the effect of different doses/modes of atosiban administration remained less clear.…”
Section: Discussionmentioning
confidence: 99%
“…of atosiban as an adjuvant in ART and they may contribute to the heterogeneity of the studies (6). Nevertheless, the reviews of previous data (6,18) also suggested that the association between atosiban and ET outcomes is not necessarily linked to the dose of atosiban administration and the effect of different doses/modes of atosiban administration remained less clear.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations